REMEDIASI MISKONSEPSI TENTANG HUKUM ARCHIMEDES MENGGUNAKAN MODEL DISCOVERY LEARNING PESERTA DIDIK SMP - Lulut, Juliana; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to study the use of Discovery Learning Model to overcome studentsâ€™ misconception in Archimedesâ€™ Principle subject in SMP Negeri 8 Pontianak academic year 2019/2020. The method used in this research was Pre-Experimental Design with One-Group Pretest-Posttest design. Logical reasoning mutiple choice questions were used as for data collection tool. Along with it, this research involved 25 students in Class IX C as the samples. They were chosen with â€œintact groupâ€ technique, a sampling method which intactly gains sample data according to population. Studentsâ€™ profile of misconception after being given remedy happened to decrease into 3 concepts. Out of 25 students that took the remedy, the percentage of studentsâ€™ with misconception in all indicators decreased by 67%. The result of calculation with McNemar Test shows 25,29 of X2 counted in all indicators then X2counted > X2 table so there is a significant conceptual changes in all the indicators. Therefore, hopefully teachers could use this research as an alternative to overcome studentsâ€™ misconception in Archimedesâ€™ Principle material. Â Keywords : Discovery Learning, Â Misconception, Â RemediationÂ